Standalone stretchable RF systems based on asymmetric 3D microstrip antennas with on-body wireless communication and energy harvesting. (1st June 2022) - Zhang, Senhao; Zhu, Jia; Zhang, Yingying; Chen, Zhensheng; Song, Chaoyun; Li, Jiuqiang; Yi, Ning; Qiu, Donghai; Guo, Kai; Zhang, Cheng; Pan, Taisong; Lin, Yuan; et al.
Abstract: As an indispensable component, the stretchable antenna with the potential use in wireless communication and radio frequency (RF) energy harvesting can provide future wearable electronics with a low profile and integrated functions. However, mechanical deformations applied to stretchable antennas often lead to a shift of their resonant frequency (i.e., the detuning effect), which limits their applications to strain sensing. In addition, the on-body radiation efficiency of stretchable antennas severely degrades due to lossy human tissues. In this work, we introduce stretchable microstrip antennas with varying 3D configurations for excellent on-body radiation performance. Compared to their 2D counterpart, the stretchable 3D microstrip antennas showcase a strain-insensitive resonance, improved stretchability, and enhanced peak gain. In particular, the optimized peak gain from the stretchable asymmetric 3D microstrip antenna allows it to wirelessly transmit the energy and data at an almost doubled distance, as well as a doubled charging rate from the harvested RF energy. More importantly, the integration of stretchable antenna and rectenna with stretchable sensing and energy storage units can yield a standalone stretchable RF system for future health monitoring of humans and structures. The results from this work can also pave the way for the development of self-powered units with wireless transmission capabilities for stretchable body area networks and smart internet-of-things. Graphical abstract: Standalone stretchable RF systems based on asymmetric 3D microstrip antennas with on-body wireless communication and self-powered sensing ga1 Highlights: The asymmetric 3D structures lead to an enhanced peak gain of stretchable microstrip antennas. The improved peak gain contributes to a longer wireless communication distance and higher RF energy harvesting efficiency. Standalone stretchable RF-powered sensing systems allow for physiological condition monitoring and body movement detection.